Violation of universal human rights and persecution of the Serbian orthodox church in Montenegro during the COVID-19 epidemic - Mirović, Dejan (Sociološki pregled, 2020)
At the end of 2019, the Law on the Freedom of Religion was adopted in Montenegro, causing protests and mass litanies from December 2019 to March 2020. After the outbreak of the COVID-19 epidemic, the authorities in Podgorica actually abolished the freedom of assembly and the freedom of religion. Thus the authorities in Montenegro, under the pretext of the urgent social need or public health protection, acted disproportionally and inappropriately during the epidemic. That was the violation of the international conventions guaranteeing universal protection of the freedom of religion and the regulations prohibiting discrimination. The COVID-19 epidemic was used by the authorities to clamp down on the Serbian Orthodox Church in Montenegro for the purpose of establishing the non-canonical Montenegrin Orthodox Church, expropriating the church property and imposing the provisions of the illegitimate and illegal Law on the Freedom of Religion.
Keywords: COVID-19; international law; Montenegro; Bishop Joanikije; human rights